Analysis and Assistance in the Formation of Draft Nagari Tungkar Regulations in Lima Puluh Regency, West Sumatra Province - Haskar, Edi; Hazmi, Raju Moh; Munandar, Syaiful (PT FORMOSA CENDEKIA GLOBAL, 2025)
This service has an output to provide an understanding of the formation of nagari regulations. The object of this service is located in the Nagari Tungkar Government, Fifty Cities Regency, West Sumatra Province with the target focused on the Nagari Tungkar Government apparatus. From the initial exploration, it was found that the Nagari Tungkar apparatus still knew little about the formation of nagari regulations. In fact, the draft nagari regulation on the Nagari Tungkar Customary Density was made not in accordance with the principles and guidelines for the formation of laws and regulations. The method of implementing this service consists of 3 (three) stages, namely Phase I of seminars/socialization, Phase II review of draft state regulations, Phase III of discussion and evaluation. The results of the service found that there is not enough literacy to make nagari regulations This contribution of service is able to increase literacy as well as contribute to forming nagari regulations that obey the principles, types, and hierarchy of laws and regulations.